Morfologi, Sifat Fisik dan Kimia Tanah Inceptisols dari Bahan Lakustrin Paguyaman- Gorontalo Kaitannya dengan Pengelolaan Tanah - ., Nurdin (Jurnal Agroteknotropika, 2012)
The Inceptisols has potential for upland agroculture, but it has problems in the field. Identification and soil characterization was need for mismanagements. Research aimed to indentify the Inceptisols characteristic derived from lakustrine as based of soil managements. Two pedons from Paguyaman of Gorontalo Province were studied both in field and in the laboratory. Twelve soil samples were analyzed for physical and chemical properties. The result of this research showed that the soil morfology of Paguyaman Inceptisols has horizon of arrangement was Ap-Bw and Ap-Bw-Br with different soil depts. Soil matrix color of two pedons dominantly of brown that indicated of B cambic horizon has formed but has not argillic horison. All pedon finded of ocrich epipedons, therefore the soil classify as Typic Eutrudept, fine loamy, smectitic, isohypertermic (PLKS) and Typic Eutrudept, fine, smectitic, isohypertermic (PLKM). Inceptisol was forming way of pedoturbation and lessivage process where done clay and C-organic movements, ground water finded in 100 cm soil depts to half time in a years and base saturation ? 60%. This Inceptisol has loamy of textures, acid until alkalis of soil pH, moderately of nutrient stock and cation exchange capacity moderate until high value. These carracteristics indicated that this soil has potential for food crop cultivations. Therefore, the pedon PLKM more potential than pedon PLKS